Magnetic hybrid nanomaterial based on a natural polymer and an amino acid as pH/temperature dual-responsive nanoplatform for the delivery of tamoxifen - Torres, Jazmín; Cadena Castro, Diego; Ancarani, Rosario; Bruvera, Ignacio; Mendoza Zélis, Pedro; Martín, Sandra E.; García, Mónica C.; Uberman, Paula M. (Frontiers in Nanotechnology, 2024)
Magnetic hybrid nanomaterials offer promising properties for the advancement of nanoplatforms in cancer nanomedicine, particularly in drug delivery applications. These nanoplatforms can effectively respond to various stimuli present at the tumor site, such as pH and temperature fluctuations, allowing for controlled and triggered release of therapeutic payloads. In this study, we present a straightforward methodology for the synthesis of stable hybrid magnetic nanoplatforms (HMNP) based on Fe3O4 nanoparticles, L-cysteine (L-Cys), and hyaluronic acid (HA) as key constituents for the delivery of tamoxifen (TMX). The synthesized superparamagnetic HMNP, Fe3O4-L-Cys-HA, with a size of 11 nm, was successfully loaded with TMX. The incorporation of L-Cys showed superior interaction with the surface of Fe3O4 nanoparticles compared to other L-Cys derivatives explored as ligands. Consequently, L-Cys was selected for further functionalization with HA, providing the HMNP with active targeting properties toward CD44-overexpressed receptors. High loading efficiency of TMX (75%) was achieved via electrostatic interaction between the carboxylate groups exposed by the HMNP and the ammonium group of the TMX side chain. Efficient control in the TMX release towards different receptor media was observed. Notably, the release of TMX from HMNP-TMX was triggered under acidic pH and hyperthermia conditions, showcasing its responsiveness to both stimuli. Furthermore, enhanced anticancer activity of TMX against MDA-MB-231 breast cancer cells was observed when loaded into HMNP (IC50 almost 3-fold lower for HMNP-TMX compared to free TMX), indicating improved cell uptake of TMX-loaded HMNP in comparison to the free drug. Overall, pH/temperature dual-sensitive HMNP demonstrates promising potential as a nanoplatform for cancer nanomedicine, with prospects for magnetic hyperthermia therapy.